WOMEN'S LEADERSHIP BASED ON INTERPERSONAL ABILITY IN BUILDING TEACHER SELF AWARENESS - Subaidah; Rizquha , Ach (Managere: Indonesian Journal of Educational Management, 2023)
This research aims to examine the important role of women's leadership in facilitating the development of self-awareness of teachers at the Alas Sumur Lor II PKK Kindergarten. Self-awareness is an essential aspect in individual personal and professional development, especially for teachers who play a role in forming the next generation. This research method uses a qualitative approach by collecting data through in-depth interviews and participant observation, consisting of female teachers at the PKK Alas Kindergarten. Sumur Lor II. The data collected was analyzed using a thematic approach, allowing the identification of patterns related to the role of women's leadership. The results of the research show that women's leadership based on interpersonal skills has a positive impact in building self-awareness in teachers. Through effective communication, empathy, and active listening skills, female leaders are able to create an environment that supports teachers' self-development. This research contributes to the understanding of the vital role of women's leadership based on interpersonal skills in the world of education.